THE EFFECT OF FIRM CHARACTERISTICS TO PROFITABILITY OF FOOD AND BEVERAGES COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Kartiningsih, Donna
Based on the data from Badan Pusat Statistik (BPS) the growth of Gross Domestic Indonesia (GDP) decreased since the third quarter of 2018 and this condition became worse because of the coronavirus pandemic situation. It was decreased from 4,97 percent in the fourth quarter of 2019 became 2,97 percent in the first quarter of 2020 and the inflation rate for food and beverage is only 0,18 percent. Food and beverages industry growth increase from year to year in line with the increasing demand for food and beverages. It is related to the fact of life that all living things need food and beverages to survive.